Potency of Example-Based Approach on Students’ Academic Achievement among Senior Secondary Students in Malumfashi, Katsina State, Nigeria - HALLIRU, Abdulkadir; IBRAHIM, A’ishatu Sada (Ilorin Journal of Education, 2025)
This study investigates the effectiveness of example-based approach on students’ academic achievement among senior secondary school students in Malumfashi, Katsina State, Nigeria, with a focus on both the main effect and gender differences. The study was guided by two research questions and two corresponding hypotheses. The study adopted quasi-experimental design. The study engaged 179 out of the total population of 2,452 Senior Secondary School 2 Chemistry students. The sample size was obtained from four intact classes which were also obtained from four coeducational public secondary schools, purposively sampled from 27 schools in Malumfashi Zonal Education Quality Assurance. Two groups of mixed gender were established; the experimental group was taught chemistry concepts using the example-based approach, and the control group was taught the same concepts with the conventional lecture method for the duration of six weeks. A validated, WAEC-adapted Chemistry Achievement Test (CAT) was used to assess the students’ academic achievement, having reliability coefficient of 0.87. All research questions were answered using the mean and standard deviation while ANCOVA was used to test null hypothesis one and Independent sampled t-test was used to test null hypothesis two at 0.05 level of significance. The results of the study indicated a significant main effect, with the experimental group outperforming the control group (p<0.05), but no significant gender difference was observed (p>0.05). Based on the results, it was concluded that the example-based approach enhances students’ understanding of Chemistry concepts, benefiting both male and female students equally. Recommendations include integrating example-based strategies into the Chemistry curriculum, ensuring gender-sensitive teacher training in science education.